2018
DOI: 10.1186/s12890-018-0589-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, burden and risk factors associated with chronic obstructive pulmonary disease in Commonwealth of Independent States (Ukraine, Kazakhstan and Azerbaijan): results of the CORE study

Abstract: BackgroundIn the Commonwealth of Independent States (CIS) countries the epidemiology of chronic obstructive pulmonary disease (COPD) is poorly characterized. The objective of this analysis is to present the prevalence, burden and risk factors associated with COPD in three CIS countries as part of the CORE study (Chronic Obstructive Respiratory Diseases), the rationale and design of which have been described elsewhere.MethodsA total of 2842 adults (≥18 years) were recruited (964 in Ukraine, Kiev, 945 in Kazakhs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
5
30
1
3
Order By: Relevance
“…In this regard, our findings are more consistent with studies in other countries than another Kazakhstan study using self-reported estimates (OR 2.3). 6 Interestingly, almost similar magnitude of effect was found in specific populations, like miners, when highly exposed workers are compared to those with low exposure, 7 or tractor plant workers. 23 In our multiple regression model, the strength of effect associated with occupational exposure may be as high as the one of smoking, and this will dictate Abbreviations: VGDF, vapors, gases, dusts and fumes; SHS, secondhand smoke; COPD, chronic obstructive pulmonary disease; OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In this regard, our findings are more consistent with studies in other countries than another Kazakhstan study using self-reported estimates (OR 2.3). 6 Interestingly, almost similar magnitude of effect was found in specific populations, like miners, when highly exposed workers are compared to those with low exposure, 7 or tractor plant workers. 23 In our multiple regression model, the strength of effect associated with occupational exposure may be as high as the one of smoking, and this will dictate Abbreviations: VGDF, vapors, gases, dusts and fumes; SHS, secondhand smoke; COPD, chronic obstructive pulmonary disease; OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 77%
“…COPD prevalence in our analysis in the age group 40 and older equaled 5.6%, more in men (8.7% vs 3.4%), which was obviously different compared to another population-based study in Kazakhstan. 6 As opposed to the first study, which was guided by postbronchodilator FEV1/FVC<0.70, we only considered COPD in those with postbronchodilator FEV1/ FVC<LLN. Despite very wide use of FEV1/FVC<0.70 as COPD criterion, also recommended by GOLD, 13 fixed ratio is known to overestimate COPD, [14][15][16] especially in the elderly, 16 as it does not account for age-related natural FEV1/FVC drop, and false-positive COPD is frequent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У Греції поширеність ХОЗЛ, за різними даними, коливається в межах від 9,6 до 17,1 % [13]. Дослідження CORE (Chronic Obstructive REspiratory diseases in CIS countries) показало, що поширення ХОЗЛ становило 10,4; 13,8 та 4,3 на 1000 населення відповідно в Україні, Казахстані та Азербайджані [14].…”
Section: вступunclassified
“…Despite high mortality rates, very limited epidemiological COPD data are available in Ukraine. The CORE study conducted across major cities in Ukraine, Kazakhstan and Azerbaijan from the first half of 2013 until the end of 2015 have showed that prevalence of COPD diagnosed by spirometry (based on the Global Initiative for Chronic Obstructive Lung Disease guideline (2011) (FEV1/FVC < 0.70)) was 31.9 (95% CI 21.7-45.3) per 1000 of population in Ukraine 15 . Remarkably, almost all (90%) of the deaths caused by COPD occurred in low and middle-income countries (LMICs) 16 .…”
Section: Introductionmentioning
confidence: 99%